Association of the neutrophil-to-platelet ratio with response to electroconvulsive therapy in adolescents with major depressive disorder - Geng, Dandan; Wang, Wenxin; Du, Ning; Niwenahisemo, Lisa Cynthia; Xu, Heyan; Wang, Yuna; Kuang, Li (Frontiers in Psychiatry, 2024)
BackgroundMajor depressive disorder (MDD) is one of the most serious mental disorders affecting adolescents worldwide. Electroconvulsive therapy (ECT) is widely acknowledged as a first-line treatment for severe depression, but the clinical response varies. Neutrophils and platelets are both related to the progression of MDD. The aim of this study was to investigate the correlation between the neutrophil-to-platelet ratio (NPR) during the acute phase and the effectiveness of ECT treatment.MethodsA total of 138 adolescent MDD patients who received ECT were included in the study. Neutrophil and platelet levels were obtained upon admission. At the same time, treatment response was the primary outcome measure, defined as a reduction of ≥ 50% in the HAMD-17 score from baseline to treatment endpoint, and the secondary outcome measure was remission of depression, defined as a HAMD-17 score ≤ 7.ResultsAfter receiving ECT, 103(74.6%) of all patients responded to treatment and 72(52.2%) achieved remission. Non-responders/non-remitters to ECT tended to have higher levels of NPR at baseline compared to ECT responders/remitters [Non-responder: 3.4 (2.5-4.8) vs 2.7 (2.2-3.5), P = 0.002; Non-remitter: 0.014 (0.011-0.017) vs 0.011 (0.008-0.015), P = 0.03]. In multiple logistic regression, high NPR (≥ 0.014) remained independently associated with ECT non-response/non-remission after adjusting for confounding factors [Non-responder: OR = 4.911, 95% CI (2.052 - 11.754), P < 0.001; Non-remitter: OR = 2.704, 95% CI (1.262 - 5.796), P = 0.011].ConclusionHigh NPR correlates with poor ECT efficacy in adolescents with MDD, particularly among female and overweight patients.